Personality Traits and Parenting Stress Among Working Mothers of Young Children - Sumedi Priyana Nugraha; Raden Rachmy Diana; Qurota’aini Zahira Muslih; Leonita Ikasari Saputri D (Universitas Ahmad Dahlan, 2024)
Working mothers with young children bear dual responsibilities, managing professional duties while attentively caring for their children, often leading to parenting stress. This study aims to examine the influence of Big Five personality traits on parenting stress among working mothers with young children. This research fills a gap in the literature regarding how personality aspects affect parenting stress. The study participants included working mothers with children aged 0-6 years, who are married, and residing in the Special Region of Yogyakarta, Indonesia. The methodology utilized the Parenting Stress Scale (PSS) and The Big Five Personality Inventory (BFI), with data analysis conducted through multiple regression techniques. The results indicate that agreeableness and extraversion negatively affect parenting stress, while openness, conscientiousness, and neuroticism do not have a significant impact. These findings underscore the importance of understanding personality traits in managing parenting stress among working mothers. The implications of this study can be used to develop more effective interventions to support the mental health of working mothers.Keywords: Parenting stress, openness, conscientiousness, extraversion, agreeableness, neuroticism.